MemoryGel Breast Implants: Final Safety and Efficacy Results after 10 Years of Follow-Up - Caplin, David A; Calobrace, M Bradley; Wixtrom, Roger N; Estes, Megan M; Canady, John W (Plastic and reconstructive surgery (1963), 2021)
Mentor MemoryGel Breast Implants were approved by the U.S. Food and Drug Administration in November of 2006. Patients in the Core clinical study supporting this approval were followed for 10 years. This prospective, multicenter, clinical study included primary augmentation, revision augmentation, primary reconstruction, and revision reconstruction patients implanted with smooth or Siltex Texture MemoryGel Implants. Incidence, severity, and method of resolution for all postoperative complications were assessed on per-patient and per-implant bases. The primary effectiveness endpoints were overall mean change in chest circumference and bra cup size following the implantation procedure. Primary augmentation (n = 552), revision augmentation (n = 145), primary reconstruction (n = 251), and revision reconstruction (n = 60) patients were enrolled in the study. Kaplan-Meier estimated 10-year cumulative incidence rates for key complications at the subject level for Baker grade III/IV capsular contracture were as follows: primary augmentation, 12.1 percent; revision augmentation, 24.4 percent; primary reconstruction, 20.5 percent; and revision reconstruction, 36.9 percent. For infection, rates were as follows: primary augmentation, 1.6 percent; revision augmentation, 1.4 percent; primary reconstruction, 6.2 percent; and revision reconstruction, 0 percent. For explantation with or without replacement, rates were as follows: primary augmentation, 11.6 percent; revision augmentation, 24.1 percent; primary reconstruction, 33.4 percent; and revision reconstruction; 37.8 percent. For rupture, rates were as follows: primary augmentation, 24.2 percent; revision augmentation, 23.7 percent; primary reconstruction, 32.7 percent; and revision reconstruction, 38.7 percent. For any reoperation, rates were as follows: primary augmentation, 25.5 percent; revision augmentation, 43.6 percent; primary reconstruction, 49.0 percent; and revision reconstruction, 50.7 percent. The results of this study demonstrate that MemoryGel Implants are safe and effective for use in women undergoing breast augmentation or reconstruction. Therapeutic, IV.